Population dynamics of centrosome amplification - Louro, Marco António Dias (2024)
"Living organisms are fundamentally composed of cells and subject to evolutionary change. These are perhaps two of the most general concepts in biology. An integrative framework that encompasses both evolutionary and cell biology is necessary for understanding how cellular features change and diversify. Such a framework is crucial for understanding a plethora of phenomena, ranging from how cellular components expand and disappear across the tree of life to human disease. In this thesis, I make use of evolutionary and cell biological principles to address the causes and consequences of centriole number abnormalities.(...)"